Replica exchange molecular dynamics simulation of structure variation from α/4β-fold to 3α-fold protein - Lazim, Raudah (2013)
Replica exchange molecular dynamics (REMD) simulation provides an efficient conformational sampling tool for the study of protein folding. In this study, we explore the mechanism directing the structure variation from α/4β-fold protein to 3α-fold protein after mutation by conducting REMD simulation on 42 replicas with temperatures ranging from 270 K to 710 K. The simulation began from a protein possessing the primary structure of GA88 but the tertiary structure of GB88, two G proteins with “high sequence identity.” Albeit the large Cα-root mean square deviation (RMSD) of the folded protein (4.34 Å at 270 K and 4.75 Å at 304 K), a variation in tertiary structure was observed. Together with the analysis of secondary structure assignment, cluster analysis and principal component, it provides insights to the folding and unfolding pathway of 3α-fold protein and α/4β-fold protein respectively paving the way toward the understanding of the ongoings during conformational variation.